How to Promote the Ability of Physics Teaching Materials Development through Team-Based Project Learning? An Action Research Evidence - Anggaryani, Mita; Satriawan, Muhammad; Saputra, Oka; Habibbulloh, Muhammad (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2024)
This action research study investigates the use of team-based project learning to enhance the pedagogical competence of pre-service physics teachers, specifically focusing on their capacity to develop physics teaching materials. The study employed a five-stage strategy, which included the following steps: first action, observation, reinforcement, second action, and assessment. These phases formed a cycle of action research in a pedagogical course within the undergraduate program of physics education, specifically focused on teaching material development. Observation, assignments, product assessment sheets, and interviews were utilized to obtain data. The obtained data consists of quantitative data, namely performance value data related to both the process and product, as well as qualitative data in the form of interview findings. The findings indicate that 96% of pre-service teachers who engaged in material development courses through project activities had highly satisfactory marks, namely within the A- and A categories. This study emphasizes the significance of fostering efficient pedagogical techniques among prospective educators and provides data from an action research investigation. Furthermore, this research also assists in the preparation of pre-service physics instructors who possess the necessary skills to create physics textbooks. Participating in collaborative project activities allows pre-service physics teachers to gain essential skills, knowledge, and practical experiences that will prepare them for their future positions in the classroom.